The Role of Student Engagement in Mediating Learning Motivation and Learning Discipline on Economic Learning Outcomes - Abdullah, Faizzal; Sari, Maylia Pramono Sari (Business and Accounting Education Journal, 2024)
Like companies in general, transportation sub-sector companies must maintain the company's financial condition so that they do not experience financial distress or the stage of decline in financial condition that occurs before bankruptcy or liquidation occurs. Financial distress is a situation where a company experiences poor financial performance which is characterized by the company experiencing losses for at least two consecutive years. Financial distress occurs before the company experiences bankruptcy. Financial distress can be measured through financial reports by analyzing financial ratios. This research was conducted to test and analyze financial ratios in predicting financial distress. This research is a type of quantitative research to analyze whether leverage, liquidity and profitability can influence financial distress. The population in this research is all transportation companies in 2020-2022 with a total of 25 companies. The sample selection technique used purposive sampling, so that 75 units were obtained and significance analysis was carried out. Data is collected first using documentation techniques. The data analysis tool used is panel data regression using the Eviews 12 program. The research results show that leverage and liquidity show a negative influence on financial distress, while profitability has no effect on financial distress. Company size is able to moderate variable leverage and financial distress. However, company size is not able to moderate the influence of liquidity and profitability on financial distress. Based on this research, investors are expected to be able to make decisions to invest by considering the financial health condition of transportation subsector companies by knowing the risk level of the possibility of the company experiencing financial distress. The government's role is important in supporting companies that are experiencing financial distress, both from a financial and non financialperspective, by providing relaxation in existing policies. And for further research you can add other independent variables such as the amount of institutional ownership, good corporate government (GCG) or those that influence financial distress. Apart from that, we can add differences in the company's financial distress conditions before, during and after the Covid-19 pandemic.